Hemodynamic and Non-Hemodynamic Components of Cardiac Remodeling in Primary Aldosteronism - Pan, Chien-Ting; Wu, Xue-Ming; Tsai, Cheng-Hsuan; Chang, Yi-Yao; Chen, Zheng-Wei; Chang, Chin-Chen; Lee, Bo-Ching; Liao, Che-Wei; Chen, Ya-Li; Lin, Lung-Chun; Chang, Yi-Ru; Hung, Chi-Sheng; et al. (Frontiers in Endocrinology, 2021)
Objectives: Patients with primary aldosteronism (PA) have cardiac remodeling due to hemodynamic and non-hemodynamic causes. However, component analysis of cardiac remodeling and reversal in PA patients is lacking. We investigated components of cardiac remodeling and reversal after adrenalectomy in patients with aldosterone-producing adenoma (APA). Methods: This study prospectively enrolled 304 APA patients who received adrenalectomy and 271 with essential hypertension (EH). Clinical, biochemical and echocardiographic data were collected in both groups and 1 year after surgery in the APA patients. The hemodynamic and non-hemodynamic components of left ventricular (LV) remodeling were represented by predicted left ventricular mass index (LVMI) (pLVMI) and inappropriately excessive LVMI (ieLVMI, defined as LVMI-pLVMI). Results: After propensity score matching, 213 APA and 213 EH patients were selected. APA patients had higher hemodynamic (pLVMI) and non-hemodynamic (ieLVMI) components of LV remodeling than EH patients. In multivariate analysis, baseline pLVMI was correlated with systolic blood pressure (SBP) and serum potassium, whereas ieLVMI was correlated with log plasma aldosterone concentration but not blood pressure. Post-operative echocardiography was available in 207 patents and showed significant decreases in both pLVMI and ieLVMI after adrenalectomy. In multivariate analysis, ΔpLVMI was correlated with SBP, ΔSBP, and pre-operative pLVMI, whereas ΔieLVMI was correlated with Δlog aldosterone-to-renin ratio (ARR) and pre-operative ieLVMI. Conclusions: This study concluded that extensive cardiac remodeling in APA patients occurs through hemodynamic and non-hemodynamic causes. Adrenalectomy can improve both hemodynamic and non-hemodynamic components of LV remodeling. Regressions of pLVMI and ieLVMI were correlated with decreases in blood pressure and ARR, respectively.